Lessons from failure: Fiscal policy, indulgence and ideology. - Wren-Lewis, S (SAGE Publications, 2011)
Macroeconomic theory clearly suggests that at the zero lower bound, fiscal contraction will reduce output and slow any recovery. Yet in 2010 the focus of fiscal policy in many countries switched from supporting activity to reducing debt, despite the fact that the recovery from recession often appeared weak. While high levels of public debt can explain this switch in some countries, it does not provide a satisfactory account in others. In addition, the possibility of using balanced budget fiscal expansion or tax switches that bring forward spending remain largely unexplored. This paper suggests that policy has been influenced by an opposition to countercyclical fiscal policy which has ideological roots.